Structure/function of ATP sulfurylase domain of human 3′-phosphoadenosine 5′-phosphosulfate synthase (hPAPSS) - K.V. Venkatachalam; Dhiraj Sinha; Chris Soha; Rudi H. Ettrich (Biochemistry and Biophysics Reports)
3′-phosphoadenosine 5′-phosphosulfate (PAPS) is synthesized by PAPS synthase (PAPSS) in two steps. In the first step ATP sulfurylase (ATPS) transfers sulfate group onto adenylyl moiety of ATP to form adenosine 5′-phosphosulfate (APS) and PPi. APS-kinase (APSK) then transfers the gamma-phosphoryl from ATP onto 3′-OH of APS to form PAPS and ADP. Mutations of histidine's (H425/H428) of hPAPSS isoform1 knocked out ATPS and not APSK. In silico ATP binding and molecular dynamics experiments exhibited an unfavorable binding energy for mutant enzymes. Thus, requirements of H425NGH428 motif for ATPS is established. The N426 residue in various organisms is substituted with R. We mutated hPAPSS1 with basic residue K. The N426 to K426 (N–K) mutant exhibited slightly lower Km (3.7 mM) and higher Vmax (3X) for ATP compared to wildtype (WT, Km 4.3 mM). The Km for sulfate for N–K mutant was nearly same as WT but the Vmax was ∼4X higher for N–K. The catalytic efficiency (Vmax/Km) of N–K was ∼3 fold higher than WT. The full length hPAPSS1 evinced bimodal response against ATP, a paradigm that was deduced to be a trait of PAPSS that requires 2 mol of ATP/PAPS formed. This bimodal kinetics with ATP was lost when the N-terminal APSK was deleted from the C-terminal ATPS domain. The C-terminal domain contained ATPS activity, exhibited Km of 2.2 mM for ATP and Km of 0.53 mM for Sulfate and much higher catalytic efficiency compared to full length hPAPSS1. Thus, fused ATPS-APSK must be structurally and kinetically different than individual domains influenced by inter-domain residues.